Quantitative Muscle Ultrasound in Duchenne Muscular Dystrophy: A Comparison of Techniques - Shklyar, Irina (Muscle Nerve, 2014)
INTRODUCTION: Muscle pathology in Duchenne muscular dystrophy (DMD) can be quantified using ultrasound by measuring either the amplitudes of sound-waves scattered back from the tissue [quantitative backscatter analysis (QBA)] or by measuring these backscattered amplitudes after compression into grayscale levels obtained from the images (GSL). METHODS: We measured and compared QBA and GSL from 6 muscles of 25 boys with DMD and 25 healthy subjects, aged 2–14 years, with age and, in DMD, with function (North Star Ambulatory Assessment). RESULTS: Both QBA and GSL were measured reliably (intraclass correlation ≥ 0.87) and were higher in DMD than controls (P<0.0001). In DMD, average QBA and GSL measured from superficial regions of muscle increased (rho ≥ 0.47, P < 0.05) with both higher age and worse function; in contrast, GSL measured from whole regions of muscle did not. DISCUSSION: QBA and GSL measured from superficial regions of muscle can similarly quantify muscle pathology in DMD.